A case of late‐onset Krabbe disease which showed subacute progression of spastic paresis with bilateral spinal cord lesions. Issue 4 (21st June 2018) - Mitsutake, Akihiko; Matsukawa, Takashi; Ishiura, Hiroyuki; Mitsui, Jun; Taira, Kenichiro; Tokushige, Shin‐ichi; Iwata, Atsushi; Terao, Yasuo; Shimizu, Jun; Sakai, Norio; Tsuji, Shoji
Abstract: We report a 16‐year‐old boy with the late‐onset form of Krabbe disease. The patient had been free of neuromuscular diseases until he showed subacute progression of spastic paraparesis at age 15. There was no evident peripheral neuropathy. Magnetic resonance imaging (MRI) of the brain and the spinal cord showed T2‐weighted high‐intensity lesions along the bilateral pyramidal tract from the internal capsule to the lumbar cord. Bilateral pyramidal tract involvement raised the possibility of late‐onset Krabbe disease. A markedly reduced galactocerebrosidase activity and a homozygous known pathogenic mutation in the GALC gene confirmed the diagnosis. This case was unique in that the progression was subacute and the lesions from the cervical to the lumbar cord were clearly shown by MRI.